2019
DOI: 10.1111/jcmm.14577
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of circular RNA expression of pulmonary macrophages in mice with sepsis‐induced acute lung injury

Abstract: Circular RNAs (circRNAs) make up a large class of non‐coding RNAs and play important roles in the pathology of a variety of diseases. However, their roles in pulmonary macrophage polarization after sepsisinduced lung injury is unknown. In this study, mice were divided into two groups: Sham control group and cecal ligation and puncture (CLP)‐induced ALI group. Macrophages were isolated from lung homogenates 24 hours after SCLP/CLP. We started with RNA‐seq of circRNA changes in macrophages and validated by RT‐PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Lipopolysaccharide (LPS), a main component of bacterial cell walls, has been identified as a key factor in ALI development, which can trigger a rapid and robust inflammatory response and impair the normal function of immune cells, such as macrophages. Results from previous studies showed that continuous activation of macrophages was one of the key steps responsible for accelerating ALI progress [9] , [10] , [11] , [12] . Macrophages perform multiple functions at different stages of ALI through the production of pro-inflammatory mediators including chemokines and cytokines such as interleukin-6 (IL-6), interleukin-12 (IL-12) and tumor necrosis factor alpha (TNF-α) [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a main component of bacterial cell walls, has been identified as a key factor in ALI development, which can trigger a rapid and robust inflammatory response and impair the normal function of immune cells, such as macrophages. Results from previous studies showed that continuous activation of macrophages was one of the key steps responsible for accelerating ALI progress [9] , [10] , [11] , [12] . Macrophages perform multiple functions at different stages of ALI through the production of pro-inflammatory mediators including chemokines and cytokines such as interleukin-6 (IL-6), interleukin-12 (IL-12) and tumor necrosis factor alpha (TNF-α) [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…reported that circRNA HECTD1 promoted silica‐induced pulmonary endothelial–mesenchymal transition via the gene HECTD1 . Additionally, the circRNAs chr17:71273374–71275287‐, chr14:57733878–57734418‐ and chr18:10119885–10132272‐ were reported to be up‐regulated in injured lung tissue after sepsis‐induced ALI, indicating the role of circRNAs in pulmonary macrophage differentiation and polarization 22 . In the present study, we found and confirmed that mmu_circ_0001679 and mmu_circ_0001212 expression was significantly up‐regulated in the lung tissues of sepsis + DMSO mice compared to that in sham mice and significantly decreased after treatment with the P2X 7 R antagonist A‐438079.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 21 observed significantly changed circRNA profiles and revealed a potential role of circRNAs in a mouse model of LPS-induced ALI. Bao et al 22 reported many circRNAs of dysregulated expression in the pulmonary macrophages of mice with sepsis-induced ALI. mRNA transcripts from genomic DNA are crucial in many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microRNA and circRNA sequencing techniques were broadly used to recognize potential targets from the complex RNA networks based on the models of varies disease (26)(27)(28). Sequencing of circRNAs were even performed in the RIEI mice model and sepsis-induced acute lung injury (29), these previous studies have successfully provided meaningful potential target or mechanism for the diseases, respectively. To our knowledge, this is the rst study analyzing the relationship of RILI and circRNAs by using RNA-seq data and computational approaches to identify the differentially expressed miRNAs and circRNAs.…”
Section: Discussionmentioning
confidence: 99%